Insect and fish by-products as sustainable alternatives to conventional animal proteins in animal nutrition. Issue 1 (14th December 2020) - Gasco, Laura; Acuti, Gabriele; Bani, Paolo; Dalle Zotte, Antonella; Danieli, Pier Paolo; De Angelis, Anna; Fortina, Riccardo; Marino, Rosaria; Parisi, Giuliana; Piccolo, Giovanni; Pinotti, Luciano; Prandini, Aldo; et al.
Abstract: This paper reviews current knowledge on two feedstuffs, that is, insect meal and fish by-products, as alternatives to conventional animal protein sources. After an introductory part that highlights the need for sustainable development of animal production, the alternative protein sources are discussed. In particular, after providing some indications on their production and supply focussing on EU, a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis was performed to identify the key factors that could help or impair the development of both protein sources production sectors. Finally, future perspectives are presented. The use of processed animal proteins derived from insects in farmed fish feeding is recognised by the EU legislation that authorises the use of proteins from seven insect species and the allowed substrates to rear insects. Insects have several advantages in nutritional value and the amino acid composition of their proteins generally meet animal requirements for good growth and health. The SWOT analysis indicated that insect meals can be considered as feed functional ingredients with beneficial properties that depend on the insect species, rearing system adopted, and the substrate used for their growth. Insects are expected to be increasingly used as a replacement for conventional animal-derived proteins, especially in aquafeeds. In the section regarding fishery and aquaculture by-products, the potential use of raw materials obtained during seafood processing is discussed. Peptides and amino acids recovered from as hydrolysed proteins can be used in animal feeds to partially substitute conventional protein feedstuffs thus providing nutrients, bioactive compounds and feed additives for animals. The SWOT analysis identified opportunities and weaknesses. Both the alternative protein sources are promising alternative feed ingredients for livestock production. Highlights: The sustainable development of animal production sector needs alternative protein sources for feeds formulation. Insects and fishery- and aquaculture by-products represent optimal alternative protein sources. A SWOT analysis has identified the key factors for the development of both protein sources production sectors.